Efficient transfection of Atlantic salmon primary hepatocyte cells for functional assays and gene editing - Alex K Datsomor; Ragnhild Wilberg; Jacob S Torgersen; Simen R Sandve; Thomas N Harvey (G3: Genes, Genomes, Genetics, 2023)
AbstractThe expansion of genomic resources for Atlantic salmon over the past half decade has enabled efficient interrogation of genetic traits by large-scale correlation of genotype to phenotype. Moving from correlation to causation will require genotype–phenotype relationships to be tested experimentally in a cost-efficient and cell context-relevant manner. To enable such future experiments, we have developed a method for the isolation and genetic manipulation of primary hepatocytes from Atlantic salmon for use in heterologous expression, reporter assay, and gene editing experiments. We chose the liver as the tissue of interest because it is the metabolic hub and many current Atlantic salmon research projects focus on understanding metabolic processes to improve traits such as the growth rate, total fat content, and omega-3 content. We find that isolated primary hepatocytes are optimally transfected with both plasmid and ribonucleoprotein using a Neon electroporator at 1,400 V, 10 ms, and 2 pulses. Transfection efficiency with plasmid and cutting efficiency with ribonucleoprotein were optimally 46% and 60%, respectively. We also demonstrate a 26 times increase in luciferase expression under the promoter of the key liver metabolic gene, elovl5b